Modification of Pb-Sb eutectic bearing-solder alloys with bismuth additions rapidly solidified from melt - Sayed, Rizk El-; W. Mahdi, Bilal; El-Bediwi, Abu-Bakr; Kamal, Mustafa (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this work, various amounts of Bi element have been added to the eutectic Pb-Sb to form bearing- solder materials. The Pb-Sb eutectic has been produced by rapid solidification using melt spinning technique with various amounts of Bi have been added to it, in the ratio 1, 2 , 3, 4, and 5 wt.%. Scanning electron microscopy (SEM), X- ray diffraction (XRD) analysis and differential scanning calorimetry (DSC) have been carried out. Microhardness measurements were also carried out using Vicker’s hardness technique. The results showed that, the ternary alloys up to 4 wt.% Bi have properties superior to binary eutectic material. Bismuth up to 4wt. % increases the Young’s modulus, Vicker’s hardness and decreases the electrical resistivity, internal friction and melting point. The ternary Pb-13.1Sb-4Bi solder alloy has a lower melting point about 237.87 ?C. Also, the results show that formation of Bi phase developed the mechanical properties and Vicker’s hardness due to addition of Bi element. The addition of Bi refines the crystal size of Sn in case of melt spun alloys as seen in scanning electron micrographs and X-ray diffraction.